Maximal oxygen uptake "classical" versus "contemporary" viewpoints - Bergh, U.; Ekblom, B.; Astrand, P. O. (Medicine & Science in Sports & Exercise, 2000)
In two articles Timothy Noakes proposes a new physiological model in which skeletal muscle recruitment is regulated by a central "govenor," specifically to prevent the development of a progressive myocardial ischemia that would precede the development of skeletal muscle anaerobiosis during maximal exercise. In this rebuttal to the Noakes' papers, we argue that Noakes has ignored data supporting the existing hypothesis that under normal conditions cardiac output is limiting maximal aerobic power during dynamic exercise engaging large muscle groups.